Effect of Nano ZnO on the Optical Properties of Poly(vinyl chloride) Films - Wasan Al-Taa’y; Mohammed Abdul Nabi; Rahimi M. Yusop; Emad Yousif; Bashar Mudhaffar Abdullah; Jumat Salimon; Nadia Salih; Saiful Irwan Zubairi (International Journal of Polymer Science)
Optical properties of pure and doped poly(vinyl chloride) (PVC) films, prepared by using casting technique, with different nanosize zinc oxide (ZnO) concentrations (1–20) wt% have been studied. Parameters such as extinction coefficient, refractive index, real and imaginary parts, Urbach energy, optical conductivity, infinitely high frequency dielectric constant, and average refractive index were studied by using the absorbance and transmittance measurement from computerized UV-visible spectrophotometer (Shimadzu UV-1601 PC) in the spectral range 200–800 nm. This study reveals that the optical properties of PVC are affected by the doping of ZnO where the absorption increases and transmission decreases as ZnO concentration increases. The extinction coefficient, refractive index, real and imaginary parts, infinitely high frequency dielectric constant, and average refractive index values were found to increase with increasing impurity percentage. The Urbach energy values are found to be decreasing with increasing ZnO concentration. The optical conductivity increased with photon energy after being doped and with the increase of ZnO concentration.